Health security in the production of meals in restaurants from a public market in the brazilian northeast (Research, Society and Development, 2020)
The present study aimed to assess the hygienic and sanitary quality of restaurants in a public market regarding the handlers of foods, fruits & vegetables and ready-to-eat foods. This is a descriptive and cross-sectional study, approved by the Research Ethics Committee, performed in 2019 in restaurants (n=15) from a public market in a capital of the Brazilian Northeast. We applied a checklist of good food manufacturing practices, adapted from the Brazilian regulatory standards, containing 23 items referring to the categories of food handlers, hygiene of fruits & vegetables as well as prepared foods. Data were assessed and classified according to the compliance with high, medium or low adequacy items. In order to check associations among variables, we used the Chi-square or the Fisher’s exact test, and the level of significance was p